2002
DOI: 10.1007/s00204-001-0311-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative stress in subjects exposed to carbon disulfide (CS 2 ) - an occupational coronary risk factor

Abstract: There is considerable epidemiological evidence that workers exposed to carbon disulfide (CS2) develop premature atherosclerosis leading to increased rates of coronary heart disease (CHD), but mechanisms underlying this association remain obscure. The present study documents that occupational exposure to CS2 modifies the oxidative status of plasma, which is a major determinant of the susceptibility to atherosclerosis. Concentrations of thiobarbituric reactive substances (TBARS), which reflect lipid peroxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Most observations for toluidines concern exposure to o-toluidine, which recently has been associated with an increased risk of bladder cancer (51) and is classified as probable carcinogen (28). CS 2 exposure is associated with increased oxidative stress (52,53), and, at least at higher exposures, with increased risk of cardiovascular diseases, health effects that also may be mediated by telomere shortening (54,55). Still, it cannot be ruled out that the effect of CS 2 in our study may be due to the fairly strong correlation to N-nitrosamines.…”
Section: Et Almentioning
confidence: 59%
“…Most observations for toluidines concern exposure to o-toluidine, which recently has been associated with an increased risk of bladder cancer (51) and is classified as probable carcinogen (28). CS 2 exposure is associated with increased oxidative stress (52,53), and, at least at higher exposures, with increased risk of cardiovascular diseases, health effects that also may be mediated by telomere shortening (54,55). Still, it cannot be ruled out that the effect of CS 2 in our study may be due to the fairly strong correlation to N-nitrosamines.…”
Section: Et Almentioning
confidence: 59%
“…OS in plasma may favor atherosclerosis and heart disease [67]. Radical cations were detected which affected DNA [68].…”
Section: Carbon Disulfidementioning
confidence: 99%
“…Both the CS 2 concentrations and exposure time contributed to the increase in MDA levels. Another study [Wronska‐Nofer et al, 2002] in workers with more than 20 years of CS 2 exposure demonstrated a significant increase in MDA levels, with a concurrent decrease in antioxidants (vitamin E, SOD, GSH‐peroxidase, and catalase). A recent report [Wronska‐Nofer et al, 2007] showed that subjects exposed to CS 2 presented with increased levels of lipid oxidation products, comparable to that observed in patients with coronarographically confirmed arteriosclerotic vascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence suggests that oxidative stress may contribute to CS 2 ‐induced atherosclerosis [Jian and Hu, 2000; Wronska‐Nofer et al, 2002]. It has been reported that the average serum levels of superoxide enzymes (CuZnSOD) in workers exposed to CS 2 both above and below 10 mg/m 3 (3.23 ppm) were significantly higher than those in the controls [Jian and Hu, 2000], and that the SOD levels decreased when the exposure index (time‐weighted average; TWA concentrations × working years) was higher than 900.…”
Section: Introductionmentioning
confidence: 99%